Collaborative optimization of thermal and economic performances of a tower solar aided coal-fired power generation system. (September 2022) - Jiang, Yue; Duan, Liqiang; Tong, Yongjing; Yang, Ming; Pang, Liping
Highlights: New operation strategy of solar aided coal-fired power generation unit is proposed. The system annual performances in different solar irradiation levels are studied. Collaborative optimization of the proposed system configurations is carried out. Multi-time scale thermal performance analyses of the proposed system are conducted. The sensitivity analyses of the economic parameters of solar field are explored. Abstract: This paper studies a novel tower solar aided coal-fired power generation (TSACPG) system with thermal energy storage (TES) system to realize the high-grade solar energy cascade utilization and puts forward an improved annual operation strategy of the system. The variations of annual electricity output from solar, annual solar to electricity efficiency and solar field levelized cost of electricity (LCOE) of the proposed TSACPG system under different solar multiples and thermal energy storage hours are explored in different level direct normal irradiation (DNI) sites. Collaborative optimizations of the TSACPG system configurations are performed by the non-dominated sorting genetic algorithm-II. The results demonstrate that the annual electricity output from solar is positively correlated with yearly DNI level and ascends with the increases of both TES hour and solar multiple. The annual solar to electricity efficiency descends with an increasing solar multiple and ascends with an increasing TES hour. The solar field LCOE will initially descend with the increase of solar multiple to the minimum and then ascend, and it will also ascend with an increasing TES hour. The improved operation strategy proposed is superior to the simple operation strategy in terms of both thermodynamic and economic performances. The pareto fronts in different level DNI sites are obtained with the simultaneous optimization of the annual electricity output from solar and the solar field LCOE. The best compromise solutions are obtained. The optimal TES hours and solar multiple values in high, medium and low level DNI sites are 14.14 h/2.64, 14.22 h/2.61 and 12.15 h/2.52, respectively. The multi-time scale analyses of the TSACPG system in different level DNI sites are conducted. The results suggest that the electricity output from solar is relatively high and the solar to electricity efficiency is comparatively low in high level DNI sites. The daily performance result implies that the system has a better performance in high level DNI site, which provides an important reference for the actual design of the system. Economic analysis reveals that the tower solar system investment payback time shows the superiority in high level DNI site and the investment payback time exhibits a trend towards shortening with an increasing coal price. Meanwhile, the sensitivity results of economic performance indexes show that the TSACPG system economic performance is closely related to the price of system components, which exhibits the impact of market changes on economic benefits for decision makers.